IMPLEMENTASI KURIKULUM MERDEKA DALAM SEKOLAH PENGGERAK - Febia Ghina Tsuraya; Nurul Azzahra; Salsabila Azahra; Sekar Puan Maharani (Jurnal Pendidikan, Bahasa dan Budaya, 2022)
The occurrence of the covid-19 pandemic caused a forced change in learning methods. The changes that occur are changes from the 2013 curriculum to an independent curriculum whose goal is to catch up on learning. This study aims to identify and examine the "Implementation of the Independent Curriculum in Mobilizing Schools". This study uses a qualitative method of content analysis. Data in content analysis is collected by collecting and analyzing documents, both written documents, drawings, works, and electronics and the results reported are in the form of an analysis of these documents. The independent curriculum is a learning method that refers to the talent and interest approach. The results and discussion of this study explain the meaning of implementation and independent curriculum in driving schools. Through the Mobilization School, it is hoped that it will be able to realize an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students.